The Effect of Learning Model Survey, Question, Read, Recite Review (SQ3R) and Critical Thingking Ability to Senior High School Students’ Learning Result - Fahriyah Fahmawati; Rusdi Rusdi; Ratna Komala (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Developing study in 21 century, the students must have a good skill which can support in developing era. One of the skills is critical thinking. The students must have the competence which can solve the problem faced it for instance environment pollution problem. The problem is one of parts from Biology with collaboration study model of SQ3R that has superior for cooperation between inactive and active students , the hope can give big contribute for the students can solve the problem. The Quasi experiment uses Anava two direction (2x2) Factorial. The research is done at SMAN 1 N Tambun Utara on September-October 2017. Data of the result research shows normal point and homogeny (P> 0,05) with sample 140.. The result of research uses the Anava experiment two direction can be gotten P = 0,000 ,it means P < 0,05 (reject Ho). So the summary (1) There can be the effect of the study model of SQ3R to The result of study. (2) There can be the effect of critical thinking to the result of study. (3) There can be interaction between SQ3R and critical thinking to the result of study. Keywords: Critical thinking, the result of study of environment pollution, SQ3R